2017
DOI: 10.1186/s13071-016-1950-2
|View full text |Cite
|
Sign up to set email alerts
|

Amoebic liver abscess in northern Sri Lanka: first report of immunological and molecular confirmation of aetiology

Abstract: BackgroundSince 1985, amoebic liver abscess (ALA) has been a public health problem in northern Sri Lanka. Clinicians arrive at a diagnosis based on clinical and ultrasonographic findings, which cannot differentiate pyogenic liver abscess (PLA) from ALA. As the treatment and outcome of the ALA and PLA differs, determining the etiological agent is crucial.MethodsAll clinically diagnosed ALA patients admitted to the Teaching Hospital (TH) in Jaffna during the study period were included and the clinical features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…In 2015, it was reported to be 3.0 per 10,000 admissions at THJ, highlighting that this region of the island is still largely endemic to E. histolytica [6]. In a longitudinal study, Kannathasan et al reported 346 confirmed ALA cases in northern SLK over a 3-year period, with 99.7% of serum samples testing positive for the IgG antibody against E. histolytica [48]. While no current data exists on other parts of the island, an early study by Rajasuriya and Nagaratnam (1962) reported 1.5% of total admissions at the General Hospital Colombo, the capital city, are due to ALA [7].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, it was reported to be 3.0 per 10,000 admissions at THJ, highlighting that this region of the island is still largely endemic to E. histolytica [6]. In a longitudinal study, Kannathasan et al reported 346 confirmed ALA cases in northern SLK over a 3-year period, with 99.7% of serum samples testing positive for the IgG antibody against E. histolytica [48]. While no current data exists on other parts of the island, an early study by Rajasuriya and Nagaratnam (1962) reported 1.5% of total admissions at the General Hospital Colombo, the capital city, are due to ALA [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…Additionally, distinguishing ALA from pyogenic liver abscesses (PLA) is crucial due to the differential approach to management in both conditions (see Table 1), despite similar clinical presentation (pyrexia, RUQ pain, hepatomegaly) [48]. While clinical findings alone may be insufficient to distinguish between PLA and ALA [93], certain clinical features can aid in differentiating the two.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Entamoeba histolytica was recently confirmed as a common cause of these clinically diagnosed liver abscesses in northern Sri Lanka. 6 Several factors have been postulated to play a role in the development of ALA in adult males who consume locally brewed beverages. The contributory role of alcohol-induced hepatic iron stores and the male hormone testosterone have been suggested as playing an important role in the pathogenesis of ALA. 7 Although human studies are lacking, testosterone level determines susceptibility to ALA in mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, clinically diagnosed ALA has been emerged one of the two most important parasitological public health problems (second only to malaria) in Jaffna, northern Sri Lanka. [11][12][13] Amebae establish hepatic infection by ascending the portal venous system. 14 Clinically; both types of liver abscesses usually present with similar picture ranging from malaise to fever, chills, abdominal pain, and vomiting.…”
mentioning
confidence: 99%